2022
DOI: 10.7554/elife.75746
|View full text |Cite
|
Sign up to set email alerts
|

A neural progenitor mitotic wave is required for asynchronous axon outgrowth and morphology

Abstract: Spatiotemporal mechanisms generating neural diversity are fundamental for understanding neural processes. Here, we investigated how neural diversity arises from neurons coming from identical progenitors. In the dorsal thorax of Drosophila, rows of mechanosensory organs originate from the division of sensory organ progenitor (SOPs). We show that in each row of the notum, an anteromedial located central SOP divides first, then neighbouring SOPs divide, and so on. This centrifugal wave of mitoses depends on cell-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Scabrous puncta can be observed as far as 2-3 cell diameters away ( 20-30 microns, Figure 1C), although most are localized within 10 microns of the bristle cell nuclei. Together these observations are consistent with previous reports that Scabrous-GFP can localize to the basal signaling filopodia of bristle precursor cells (Lacoste et al, 2022), and that Scabrous acts cell non-autonomously (Renaud and Simpson, 2001). Interestingly, the average length of signaling filopodia extending from the basal surface of bristle precursor cells is 10 µm April 20, 2023 4/13 (Hunter et al, 2019).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Scabrous puncta can be observed as far as 2-3 cell diameters away ( 20-30 microns, Figure 1C), although most are localized within 10 microns of the bristle cell nuclei. Together these observations are consistent with previous reports that Scabrous-GFP can localize to the basal signaling filopodia of bristle precursor cells (Lacoste et al, 2022), and that Scabrous acts cell non-autonomously (Renaud and Simpson, 2001). Interestingly, the average length of signaling filopodia extending from the basal surface of bristle precursor cells is 10 µm April 20, 2023 4/13 (Hunter et al, 2019).…”
Section: Resultssupporting
confidence: 92%
“…We and others have observed that Scabrous is distributed both apically and basally in the patterning notum. In a previous study, Scabrous was shown to localize along the length of basal signaling filopodia in the patterning notum (Lacoste et al, 2022). It is currently unknown if Scabrous is distributed via these signaling filopodia, or through a diffusion-based process.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…One limitation of this study is that the sample sizes of single-Wave analyses are not high. While clonal analysis has been used to examine fine morphological abnormalities associated with axon guidance defects (Lacoste et al, 2022; Lin et al, 2022; Seroka and Doe, 2019; Xie et al, 2019), these studies were mostly qualitative. This was because the “hit rate” is generally low in this stochastic labelling method.…”
Section: Discussionmentioning
confidence: 99%